Fit In Business Plan - Xu, Shanshan (2017)
Fit In was created in August 2017 with the share capital of RMB 200,000 that was raised from families and will be used constantly by stages. In this Business plan, we set out the operating, strategic and financial targets for the period 2018-2022 in this business plan. We are looking for additional investment for the business.